DIALOGICAL SPEECH IN LITERATURE: A COGNITIVE - DISCURSIVE APPROACH (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This This article analyzes the essence of dialogic speech in literature, its cognitive and discursive aspects. Dialogic speech is considered not only as a means of revealing the character of characters, but also as an important element that forms the semantic layers of the text. Within the framework of the cognitive - discursive approach, dialogic speech is studied in connection with human thinking, the process of perception, and communication strategies.